The implementation of TPS (think pair share) cooperative learning model aided by Google hangouts in literary expression course - Fina Hiasa; Supadi Supadi; Nafri Yanti (JOALL (Journal of Applied Linguistics and Literature), 2022)
This study aims to determine how the application of the TPS (Think-Pair-Share) type of cooperative learning model assisted by Google Hangout can improve the quality of learning in seventh semester students of the Indonesian Language Education Study Program, FKIP UNIB, in the Literary Expression course. The data analysis technique used in this study was a descriptive method that produced an overview of the extent to which the quality of learning has improved by using the TPS (Think-Pair-Share) type of cooperative learning model assisted by Google Hangouts for students who were the research samples. This classroom action research was carried out in two cycles, and each cycle used the main digital learning room, namely the Google Hangout application. Data collection techniques were carried out through non-test techniques at the beginning and end of cycles I and II using questionnaires and observation sheets. In the first cycle, the results obtained had not reached the expected target. The target required was reached in the second cycle. The learning outcomes of the second cycle of students obtained an A score of 13 people (36%), a B value of 18 people (50%), a C value of 5 people (14%), and a D value of 0 people (0%). These results indicate that the target achievement of 30% had been successfully achieved by applying the TPS learning model assisted by the Google Hangouts.